Kinerja Sub DAS Siak Bagian Hulu Dalam Pengelolaan DAS Siak - Khairullah, M; Suprayogi, Imam; Sujatmoko, Bambang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Siak river is one of the major rivers that gain national attention and was also included in the category of national strategic river, because the river has a function and a very large role in the development of the region and the economy both locally, regionally and nationally. The research objective is to monitor performance subzone Siak Hulu Part In Siak River Basin Management uses two criteria, namely the use of land and water management. Land use criteria determined by indicator closure by vegetation, suitability of land use, and the index of erosion, while water management criteria determined by indicator of river water discharge. DAS performance results Siak Hulu Section obtained a weighted sum of 26%, a total score of 12, the total value of the indicator 58 and the category is rather good. DAS performance results Siak Hulu section obtained with a value of 2.23, the value category classification DAS performance Siak Hulu section has a subzone category are "Rather Good". Performance Part subzone Siak Hulu quite a bit better illustrates that than the four indicators used in the assessment of the performance of subzone Siak Hulu section is one of the better parameters.Keywords : Watershed, Siak River, DAS Performance Parts Siak Hulu.